JOB ANALYSIS MODEL AT THE MINISTRY OF YOUTH AND SPORTS - Oktavian, Ade; Giyanto, Bambang; Saksono, Afsdy (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This research evaluates the job analysis practices at the Ministry of Youth and Sports (Kemenpora). Findings reveal that the current job analysis is not optimal due to incomplete exploration of the Ministry's mandated tasks, leading to unclear mapping of responsibilities and a lack of adherence to the PermenpanRB No. 1 of 2020 guidelines. Data collection, primarily executed by an internal team using templated methods, raises concerns about information validity and reliability. Three main agents provide job analysis information: the jobholder, their superior, and the job analyst. A challenge identified is the limited comprehension of organizational strategy and job functions among jobholders and superiors, combined with the inadequate competency of job analysts. Additionally, the research found that the data's validity and reliability are compromised due to insufficient verification processes. As a remedy, a four-stage job analysis model is proposed, encompassing preparation, data collection, data processing, and result distribution, aiming for more accurate and comprehensive job analyses. Keywords: Job Analysis, Model, the Ministry of Youth and Sports.